The folding of GroEL-bound barnase as a model for chaperonin-mediated protein folding. - Corrales, F J (1995)
We have analyzed the pathway of folding of barnase bound to GroEL to resolve the controversy of whether proteins can fold while bound to chaperonins (GroEL or Cpn60) or fold only after their release into solution. Four phases in the folding were detected by rapid-reaction kinetic measurements of the intrinsic fluorescence of both wild type and barnase mutants. The phases were assigned from their rate laws, sensitivity to mutations, and correspondence to regain of catalytic activity. At high ratios of denatured barnase to GroEL, 4 mol of barnase rapidly bind per 14-mer of GroEL. At high ratios of GroEL to barnase, 1 mol of barnase binds with a rate constant of 3.5 x 10(7) s-1.M-1. This molecule then refolds with a low rate constant that changes on mutation in parallel with the rate constant for the folding in solution. This rate constant corresponds to the regain of the overall catalytic activity of barnase and increases 15-fold on the addition of ATP to a physiologically relevant value of approximately 0.4 s-1. The multiply bound molecules of barnase that are present at high ratios of GroEL to barnase fold with a rate constant that is also sensitive to mutation but is 10 times higher. If the 110-residue barnase can fold when bound to GroEL and many moles can bind simultaneously, then smaller parts of large proteins should be able to fold while bound.